Stability of temporary submarine slopes - Bubel, Julian; Rudolph, Christina; Grabe, Jürgen (Volume 7: CFD and VIV; Offshore Geotechnics, 2011)
Shallow foundation structures for offshore wind turbines offer ecological benefits compared to pile foundations as less noise is emitted at sea floor level during construction process. On the other hand, shallow offshore foundations can rarely be placed on top of the sea floor. Weak soils usually need to be excavated to place the foundation structure on more stable ground and thus, anthropogenic submarine slopes result. Steep but stable slopes meet both economic and ecologic aims as they minimise material movement and sediment disturbance. After Terzaghi [1] the angle b between slope and the horizontal of the ground surface of coarse-grained soil is at most equal to the critical state friction angle jc. However, it can be observed that natural submarine slopes of sandy soils are always much more shallow. Particularly fine-grained, cohesionless or almost cohesionless soils failed in the past, although the slope angle was much smaller than the critical state friction angle jc. Artificial (temporary) slopes do not appear and behave as natural submarine slopes, since the latter are already shaped by perpetual loads of waves, tide and mass movements. Physical simulations of different scales are used to analyse the stability of artificial submarine slopes with sandy soil of the North Sea. The study focuses on gravitational forces and impacts from the excavation processes. The simulations and theoretical considerations result in suggested slope angles for future shallow offshore foundations of wind farms in the North Sea.